Transformation of Women's Religious Authority in Digital Da'wah: an Analysis of Ustadzah Oki Setiana Dewi - Putri Nasution, Mutia El Ilmi; Tumanggor, Rusmin (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This study examines how female preachers in Indonesia cultivate and sustain religious authority in the digital sphere, particularly within a patriarchal context where their visibility and legitimacy remain contested. While online da’wah and personal branding have been widely studied, little research addresses the intersection of gender, charisma, and mediatized communication, especially across multiple platforms. Focusing on Ustadzah Oki Setiana Dewi a prominent preacher active on YouTube, Instagram, TikTok, Threads, and Facebook. This research explores how Weber’s concept of charismatic authority is embodied and reconfigured online, and how Hjarvard’s mediatization of religion explains these processes. Using qualitative content analysis of 30 purposively selected posts over three months, complemented by non-participatory netnographic observation, the study captures thematic depth and multimodal performance, integrating narrative and visual analysis with media theory. Findings show that Oki's digital charisma is built through emotional storytelling, consistent aesthetic branding, and active audience engagement. This enables her to bypass certain institutional constraints while remaining shaped by platform logics. These results affirm Weber's view of charisma as relational and mediatization theory's emphasis on the media's active role. Limitations include the single case design, the absence of audience interviews, and the restricted timeframe. The study urges religious institutions to engage female preachers, enhance digital literacy, and explore comparative or longitudinal research on women's digital religious authority.